Factors associated with health-related quality of life in a cohort of cancer survivors in New Jersey - Sharon Manne; Katie Devine; Shawna Hudson; Deborah Kashy; Denalee O’Malley; Lisa E. Paddock; Elisa V. Bandera; Adana A. M. Llanos; Angela Fong; Neetu Singh; Sara Frederick; Andrew M. Evens (BMC Cancer, 2023)
Abstract Background Although there is extensive literature on correlates of health-related quality of life (HRQoL) among cancer survivors, there has been less attention paid to the role of socioeconomic disadvantage and survivorship care transition experiences in HRQoL. There are few large cohort studies that include a comprehensive set of correlates to obtain a full picture of what is associated with survivors’ HRQ0L. This cohort study of recent cancer survivors in New Jersey aimed to explore the association between social determinants of health, health history, health behaviors, survivorship care experiences, and psychosocial factors in HRQoL. Methods Eligible survivors were residents of New Jersey diagnosed with genitourinary, female breast, gynecologic, colorectal, lung, melanoma, or thyroid cancers. Participants completed measures of social determinants, health behaviors, survivorship care experiences, psychosocial factors, and HRQoL. Separate multiple regression models predicting HRQoL were conducted for each of the five domains (social determinants, health history, health behaviors, survivorship care experiences, psychosocial factors). Variables attaining statistical significance were included in a hierarchical multiple regression arranged by the five domains. Results 864 cancer survivors completed the survey. Lower global HRQoL was associated with being unemployed, more comorbidities, a less healthy diet, lower preparedness for survivorship, more unmet support needs, and higher fear about cancer recurrence. Two psychosocial factors, unmet support needs and fear of recurrence, played the most important role in HRQoL, accounting for more than 20% of the variance. Both unmet support needs and fear of recurrence were significant correlates of physical, functional, and emotional HRQoL domains. Conclusions Interventions seeking to improve cancer survivors’ HRQoL may benefit from improving coordinated management of comorbid medical problems, fostering a healthier diet, addressing unmet support needs, and reducing survivors’ fears about cancer recurrence.